Advancing provitamin A biofortification in sorghum: Genome‐wide association studies of grain carotenoids in global germplasm. Issue 1 (26th March 2020) - Cruet‐Burgos, Clara; Cox, Sarah; Ioerger, Brian P.; Perumal, Ramasamy; Hu, Zhenbin; Herald, Thomas J.; Bean, Scott R.; Rhodes, Davina H.
Abstract: Vitamin A deficiency is one of the most prevalent nutritional deficiencies worldwide. Sorghum [ Sorghum bicolor L. (Moench)] is a major cereal crop consumed by millions of people in regions with high vitamin A deficiency. We quantified carotenoid concentrations in a diverse sorghum panel using high‐performance liquid chromatography and conducted a genome‐wide association study (GWAS) of grain carotenoids to identify genes underlying carotenoid variation. There was moderate variation for β‐carotene (00.8 μg g −1 ), lutein (0.3–9.4 μg g −1 ), and zeaxanthin (0.2–9.1 μg g −1 ), but β‐cryptoxanthin and α‐carotene were nearly undetectable. Genotype had the largest effect size, at 81% for zeaxanthin, 62% for β‐carotene, and 53% for lutein. Using multiple models, GWAS identified several significant associations between carotenoids and single nucleotide polymorphisms (SNPs), some of which colocalized with known carotenoid genes that have not been previously implicated in carotenoid variation. Several of the candidate genes identified have also been identified in maize ( Zea mays L.) and Arabidopsis ( Arabidopsis thaliana ) carotenoid GWAS studies. Notably, an SNP inside the putative ortholog of maize zeaxanthin epoxidase ( ZEP ) had the most significant association with zeaxanthin and with the ratio between lutein and zeaxanthin, suggesting that ZEP is a major gene controlling sorghum carotenoid variation. Overall findings suggest there is oligogenic inheritance for sorghum carotenoids and suitable variation for marker‐assisted selection. The high carotenoid germplasm and significant associations identified in this study can be used in biofortification efforts to improve the nutritional quality of sorghum.